Nematóides e artrópodes em Struthio camelus Linnaeus, 1758 (avestruz) de criatórios comerciais do Rio Grande do Sul - Pesenti, Tatiana Cheuiche (2008)
Ostrich is an ratit bird that originated from Africa. In Brazil is found manly in commercial farms. The number of farms that raise ostriches is growing in Brazil due to the great reproductive potential of these birds and the great economic value of its products. Because of this increase in raising of ostriches, parasites have appeared of which little is known or studied, thus raising the need for study and description of these parasites to the scientific community and breeders. With the objective of studying the presence of parasitess in ostriches from commercial farms in the Rio Grande do Sul State, heads, respiratory and digestive systems were examined individually from 34 ostriches as well as a collection of their feathers. The material was collected during the slaughter in the Castilhense Abattoir, located in the city of Julio de Castilhos, RS. The contents and mucous membrane of the small intestine, cecum and large intestine were examined; as well as the mucous of the esophagus, proventriculus and gizzer; lung, trachea and pancreas were examined; as well as the exterior, oral, nasal and ocular cavities of the head. Nematodes were found in the digestive and respiratory systems and lice and mites in feathers. The nematodes were clarified with lactophenol and identified as Libyostrongylus douglassii, L. dentatus and Codiostomum struthionis. The lice were clarified using metil salicilate, the mites with lactophenol and identified respectively as Struthiolipeurus rheae and Struthiopterolichus sculpturatus. This is the first description of C. struthionis in ostriches in the Rio Grande do Sul state and L. dentatus in Brazil, as well as the simultaneous parasitism of L. douglassii and L. dentatus in the same host in these country. This is also the first report of S. rheae and S. sculpturatus in ostriches from the Rio Grande do Sul state.